Meningkatkan Kemampuan Berhitung 1-20 Pada Anak TK B Melalui Media Piring Angka di TK Yasuka III Surabaya - Utamiati, Utamiati; Virdaus, Varia Virdania (MOTORIC, 2024)
ABSTRACT The development of learning models needs to be done to increase students' understanding and increase creativity in solving problems in the learning process. This study aims to improve numeracy skills in Kindergarten B class children by using paper plates and clothespins as learning media at Yasuka III Kindergarten Surabaya. This research method uses classroom action research with observational data collection techniques, interviews, and documentation studies. The results in this study after 2 class actions were carried out. The ability to recognize the concept of numbers 1-20 in the Pre-Cycle, there were 3 children (20%) increased to 6 children (40%) in Cycle I, and in Cycle II there were 12 children (80%) . The ability to count many objects 1-20 in the Pre Cycle there were 4 children (26.6%) increased to 8 children (53.3%) in Cycle I, and in Cycle II there were 12 children (80%). And the ability to write numbers 1-20 in the Pre Cycle there were 6 children (40%) increased to 10 children (66.6%) in Cycle I, and in Cycle II there were 13 children (86.6%). There is an increase in numeracy skills in class B with paper plates in the experiments that have been carried out. Keywords: Numeracy Skills, Kindergarten B Children, Number Plates